Silence as a Room #1 of #5 : Q and A with Ari Sitas - Bijoux, Coral Anne (New Agenda: SA Journal of Social and Economic Policy, 2025)
An unknown individual drove a grader across a veld in the Karoo outside Richmond and levelled an art installation that had been carved and constructed over three long, hard years into the heat-baked desert soil. Ari Sitas interviewed the artist, CORAL ANNE BIJOUX, who developed the land artwork in the Karoo veld, after months of consultation, research, and development, to emulate a womb in the earth. However, her decision to create it in the open veld instead of on a private farm to allow equal and free access to all resulted in bitter consequences.